Agricultural policy in the era of digitalisation. (April 2021) - Ehlers, Melf-Hinrich; Huber, Robert; Finger, Robert
Highlights: We examine potential effects of digitalisation on agricultural policy. Digitalisation supports novel designs of instruments in multiple policy dimensions. Opportunities to improve targeting and tailoring of policy instruments arise. We provide an outlook on digitalised agricultural policy instruments and designs. Abstract: Digitalisation in the agricultural sector continues to expand. At the same time demands for an agricultural policy offering better support for sustainability become increasingly fervent. However, it is far from clear how digitalisation could make agricultural policy more effective in reducing undesired impacts and enhancing the benefits of farming. This article investigates the extent to which digital technologies can trigger different choices of agricultural policy instruments and novel design specifications that address problems of sustainability in farming more effectively and possibly more efficiently. It develops and applies an analytical framework that focuses on the effects of digitalisation in distinct policy dimensions, drawing on theoretical insights and examples from practice in a European context. We show that digital agricultural policy does not simply replace analogue technologies used in traditional agricultural policy. It offers new options for agricultural policy, including novel designs to address challenges more effectively. In particular, it offers opportunities for more effective spatial targeting and tailoring of instruments, including results-based subsidies. Digital data can be generated strategically using respective instrument designs to support policy learning and adaptation of designs. Information-intensive instruments and designs generally benefit most from digitalisation while transaction costs often go down. Digitalisation could also move agricultural policy from direct intervention to information-based governance. However, the analysis suggests that institutional constraints and interests, as well as the capabilities of the actors involved require attention in research and practice of digitalisation of agricultural policy.